Araport11: a complete reannotation of the Arabidopsis thaliana reference genome - Cheng, Chia‐Yi; Krishnakumar, Vivek; Chan, Agnes P.; Thibaud‐Nissen, Françoise; Schobel, Seth; Town, Christopher D. (The Plant journal : for cell and molecular biology, 2017)
Summary The flowering plant Arabidopsis thaliana is a dicot model organism for research in many aspects of plant biology. A comprehensive annotation of its genome paves the way for understanding the functions and activities of all types of transcripts, including mRNA, the various classes of non‐coding RNA, and small RNA. The TAIR10 annotation update had a profound impact on Arabidopsis research but was released more than 5 years ago. Maintaining the accuracy of the annotation continues to be a prerequisite for future progress. Using an integrative annotation pipeline, we assembled tissue‐specific RNA‐Seq libraries from 113 datasets and constructed 48 359 transcript models of protein‐coding genes in eleven tissues. In addition, we annotated various classes of non‐coding RNA including microRNA, long intergenic RNA, small nucleolar RNA, natural antisense transcript, small nuclear RNA, and small RNA using published datasets and in‐house analytic results. Altogether, we identified 635 novel protein‐coding genes, 508 novel transcribed regions, 5178 non‐coding RNAs, and 35 846 small RNA loci that were formerly unannotated. Analysis of the splicing events and RNA‐Seq based expression profiles revealed the landscapes of gene structures, untranslated regions, and splicing activities to be more intricate than previously appreciated. Furthermore, we present 692 uniformly expressed housekeeping genes, 43% of whose human orthologs are also housekeeping genes. This updated Arabidopsis genome annotation with a substantially increased resolution of gene models will not only further our understanding of the biological processes of this plant model but also of other species. Significance Statement The most recent annotation of the Arabidopsis thaliana genome (TAIR10), released more than 5 years ago, had a profound impact on Arabidopsis research. Here we present Araport11, a re‐annotation of the Col‐0 reference genome. We used extensive RNA‐seq data to update and extend structural gene models, thus identifying over 700 novel protein‐coding genes, 500 novel transcribed regions, 5000 non‐coding genes, and 35 000 small RNA loci that formerly eluded annotation.